An investigation of cermet and composite HVOF thermal spray coatings for internal surfaces - Pulsford, Jamie C H (2020)
High velocity oxy-fuel (HVOF) thermal spraying is a surface engineering technique which can be used to deposit coatings to provide protection from wear or corrosion. Powder particles are accelerated using a spray torch and are fired towards the required surface. WC-Co-Cr is a commonly used material that is deposited using this technique to act as a wear resistant barrier. The use of composite WC-Co/NiCrFeSiB coatings has also been a topic of interest for applications that require resistance to wear at high temperatures. In recent years, manufacturers have sought to develop thermal spray processes for internal surfaces, and this was followed by the development of internal diameter (ID) HVOF thermal spray torches that have smaller dimensions than the previously commercially used spray systems. This allowed the deposition of HVOF thermal spray coatings onto surfaces which were previously considered impossible to coat in this manner. Little is currently known regarding the effects of spraying in these conditions due to the recent development of the new ID spray systems. In this EngD thesis, three types of WC-Co-Cr powder feedstock differing in WC grain size and overall particle size were sprayed with an ID-HVOF thermal spray torch. Detailed microstructural characterisation of the sprayed coatings followed by the measurement of coating mechanical properties and dry sliding wear testing at three loads was performed. It was determined that using a powder feedstock that is smaller in size produced coatings with a high microhardness but led to greater decarburisation of the WC phase reducing the fracture toughness. This was because the smaller particles require less energy for heating and acceleration, leading to higher in-flight temperatures and velocities. The coatings sprayed using the smaller particle feedstock however performed to a good relative standard in the dry sliding wear testing, leading to it being selected for internal spray experiments. The selected WC-Co-Cr powder was then sprayed onto discs mounted on the inside of three cylindrical tubes with different internal diameters of 70mm, 90mm and 110mm. Spraying within the smallest diameter tube produced coatings with the lowest microhardness and highest porosity. This was likely due to particles being unable to accelerate sufficiently when spraying within the smallest tube due to the reduced stand-off distance. Brittle η-phase carbides were found within all three internally sprayed coatings possibly formed by substrate overheating due to the increased challenges of substrate cooling processes in ID-HVOF thermal spraying. To investigate the effects of spraying a composite powder feedstock, a WC-Co/NiCrFeSiB feedstock was sprayed using the ID-HVOF torch using two different spray parameter sets. Detailed microstructural characterisation and measurement of mechanical properties revealed that increasing the overall gas flowrate produced coatings with a higher microhardness which also exhibited better sliding wear resistance. This is due to greater in-flight velocities observed with the increase in flowrate.